Oedipality in Red Sorghum and ]udou - Farquhar, Mary (Cinémas, 1993)
This article analyses the representation of masculinity in Red Sorghum and Judou, two films directed by Zhang Yimou. The focus is on oedipality, in particular the murder of the real or symbolic "father" as a condition for the liberation of the son and his wife / mistress. The text is divided into three sections: patriarchy and the social order; patriarchy and the body; and patriarchy and legitimacy. The argument is that oedipality in these films is not presented as a "universally valid" psychic condition (Freud) but as an inevitable result of the patriarchal family system.